Mechanical properties of a thermosetting polymer reinforced with nanoclay under compressive loading - Tabares, Emee Grace
In order to contribute towards the fundamental understanding of the structure property relationship in polymer-clay nanocomposites particularly for the thermosetting matrix, unsaturated polyyester (UP) resin containing organomodified montmorillonite (MMT) systems were prepared using solution intercalation method. The nanoclay was dsipersed in the matrix suing two mixing methods (i.e. mechanical and ultrasonication) at various filler loadings (i.e. 1%, 3%, 5%, 7% and 9% by volume). Morphological characterizations and calorimetric measurements under compressive loading. Based on the TEM micrographs taken at 2.5 Kx, high frequency ultrasonication (method B) was more effective in homogeneously dispersing the nanoclay in the matrix. When these samples were viewed at a higher magnification, intercalation and partial exfoliation were observed. On the other hand, the nanocomposites prepared using mechanical mixing (Method A) exhibited a flocculated morphology. The intercalation of polymer was substantiated by XRD results, where a 44% and 52% increase in the d-spacing was observed for methods A and B respectively. The modulus and the strength were found to be strongly dependent on the degree of crosslinking, as pure UP exhibited superior values for these properties at 1.30 GPa±0.10 and 179.75 MPa±22.14, respectively. The mechanical properties exhibited by the nanocomposites was attributed to the change in the three-dimensional network of UP, as indicated by their less exothermic heat of curing. The addition of nanoclay resulted in the reduction of the degree of covalent crosslinking, the formation of physical crosslinks between the filler and the matrix and the lengthening of the crosslink bridges. these factors imposed less restriction on the movement of the polymer chains and allowed them to easily slip past each other. This gave the nanocomposites an enhanced capasity to undergo elastic deformation under low compressive loads applied, similar to the behavior manifested by elastomers.